MODERN ISLAMIC BOARDING SCHOOL WITH GREEN BUILDING CONCEPT IN KUDUS REGENCY - Almahdi, Ahmad; Hendriani, Adinda Septi; Hermawan, Hermawan (Nacreva Publisher, 2024)
The planning and design of a modern green building Islamic boarding school in Kudus Regency is a place for Islamic education with a combination of learning special skills such as language learning. Planning for a modern green building cottage is a new breakthrough in the world of Islamic education in Kudus Regency. Modern Islamic boarding schools have Islamic teachings as their main and there is additional learning skills such as language in the process. With the concept of green building can provide more comfort, because it can minimize the impact of weather that occurs in the region. It is hoped that the green building concept can make building users comfortable in carrying out their activities in the building area. Facilities in the Islamic boarding school area include comfortable dormitories, special laundry rooms, special cooking areas, halls, guest houses, large parking lots, and a visiting garden for parents who want to see their children. Taman jenguk is intended so that users from outside the area can feel as comfortable as guardians of students who have traveled long distances. Modern green building Islamic boarding schools in Kudus Regency are expected to become educational areas that prioritize Islamic teachings with the addition of skill-based learning. Skill-based learning is intended so that students who study at the Islamic boarding school do not only have religious knowledge, but also world knowledge.